(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Tomato consumption in Ukraine is consistently high. Greenhouses allow growing tomatoes throughout the year, which is especially important in winter. This article describes the morphological and biological characteristics of tomatoes. The global tomato production market is analyzed, and the global cultivation areas by country are highlighted. The greenhouse complexes where pink large-fruited tomatoes are grown in Ukraine are presented. Promising hybrids of pink large-fruited tomatoes for growing in winter greenhouses are described. The export and import markets are analyzed. It is determined that the leader in tomato imports is Turkey. The highest yield of tomatoes is achieved in the Netherlands. The average quarterly price for pink tomatoes over the past four years is highlighted. The data on the largest producers of pink tomato in winter greenhouses in Ukraine are presented.